Two-Photon Autofluorescence Imaging of Fixed Tissues: Feasibility and Potential Values for Biomedical Applications - Li, Lin Z.; Masek, Marissa; Wang, Ting; Xu, He N.; Nioka, Shoko; Baur, Joseph A.; Ragan, Timothy M. (Advances in experimental medicine and biology, 2020)
The value of optical redox imaging (ORI) of cells/tissues based on the intrinsic fluorescences of NADH (nicotinamide adenine dinucleotide) and oxidized flavoproteins (containing flavin adenine dinucleotide, i.e., FAD) has been demonstrated for potential biomedical applications including diagnosis, prognosis, and determining treatment response. However, the Chance redox scanner (a 3D cryogenic tissue imager) is limited by spatial resolution (~50 μm), and tissue ORI using fluorescence microscopy (single or multi-photon) is limited by the light penetration depth. Furthermore, viable or snap-frozen tissues are usually required. In this project, we aimed to study whether ORI may be achieved for unstained fixed tissue using a state-of-the-art modern Serial Two-Photon (STP) Tomography scanner that can rapidly acquire multi-plane images at micron resolution. Tissue specimens of mouse muscle, liver, and tumor xenografts were harvested and fixed in 4% paraformaldehyde (PFA) for 24 h. Tissue blocks were scanned by STP Tomography under room temperature to acquire the autofluorescence signals (NADH channel: excitation 750 nm, blue emission filter; FAD channel: excitation 860 nm, green emission filter). We observed remarkable signals with significant intra-tissue heterogeneity in images of NADH, FAD and redox ratio (FAD/(NADH+FAD)), which are worthy of further investigation for extracting biological information.